Resolution of Chronic Shoulder Pain after Repair of a Posttraumatic Diaphragmatic Hernia: A 22-Year Delay in Diagnosis and Treatment - Brody W. King; John G. Skedros; Robert E. Glasgow; D. Glen Morrell (Case Reports in Orthopedics)
Diagnosing traumatic diaphragmatic rupture (TDR) due to penetrating rib fractures is challenging because the lesions are often too small to be detected and may present years after injury. Patients with delays in diagnosis of TDR rarely present with orthopaedic-related complaints of pain. We report the case of a 52-year-old female who presented with chronic left shoulder pain following a motor vehicle accident (MVA). In addition to left-side lower rib fractures, she also sustained a left-sided splenic laceration, pneumothorax, and two-part upper humerus fracture. Fracture treatment was percutaneous pinning; the other injuries were treated nonoperatively. Her shoulder pain could not be attributed to shoulder or neck pathology. Twenty years after the MVA, she began experiencing episodes of left-sided abdominal pain and nausea. A CT scan obtained two years later revealed a diaphragm hernia, which was repaired laparoscopically. Unique aspects of this case include (1) presentation to an orthopaedic surgeon with a chief complaint of chronic shoulder pain; (2) at 22 years, this is the fourth longest case of a delay in diagnosis of TDR; and (3) the unique symptom of ipsilateral referred shoulder pain, which immediately improved after hernia repair.